Vulnerability in the Urban Environment: A Comparative Analysis - Rae, Christopher (Tufts Archival Research Center, 2005)
In 2007, the Internal Displacement Monitoring Center estimated that the total number of individuals who had been forcibly displaced from their homes, but remained within the territory of boundaries of their country, surpassed 27 million. (Jennings, 2008) Known as Internally Displaced Persons (IDPs), their numbers have been steadily growing since the early 1990s. Defined by the Guiding Principles on Internal Displacement (Guiding Principles) as persons or groups of persons who have been forced or obliged to flee or to leave their homes or places of habitual residence, in particular as a result of or in order to avoid the effects of armed conflict and who have not crossed an internationally recognized state border", IDPs have overtaken refugees as the largest constituent of forced migrants throughout the world. (Jennings, 2008; United Nation, 1998:2) But what specifically are the protection needs of the displaced?  What deprivations have they suffered during their flight, and what distinguishes them from other conflict-affected populations? The purpose of this study is to better understand the experience of IDPs living in urban centers, the specific risks they face, and the means with which they mitigate those challenges. This study examines if IDPs are more vulnerable than voluntary (economic) migrants or their long-term resident neighbors, and analyzes what factors most influence vulnerability in the urban context. To compare the relative vulnerability of urban residents, the author constructed a vulnerability index oriented around risk indicators and influencing factors drawn from the survey tools used in the IDMC-Tufts urban IDP profiling study, which collected data from 3 urban centers known to host large numbers of forced migrants: Santa Marta (Colombia), Khartoum (Sudan), and Abidjan (Ivory Coast.)(Jacobsen, 2008(1); Jacobsen, 2008(2); Jacobsen, et al, 2008(3). The index was used in a 3 model regression analysis of the Tufts-IDMC study data: an initial model to test the validity of the index, followed a regression analysis for each indicator of the index, and a final analysis using a composite variable built on the six indicators of the index. Though a degree of variability was anticipated, IDPs were expected to be more vulnerable than other city residents across a range of indicators, and that factors such as time displaced, household composition, and education would have a particularly significant influence on vulnerability. The findings of this study varied considerably across each of the vulnerability indicators, as well as the influencing factors included in the index. The results did not fully support the hypothesis, in that IDPs were not consistently more vulnerable than other residents, but proved less vulnerable than other residents on a number of variables, including their access to water and steady employment. Education was found to be an important influence on vulnerability, in that a respondent's level of education was strongly correlated with low vulnerability. The findings did not demonstrate a strong relation between vulnerability and the length of time of displacement, nor was it able to adequately illuminate how a household's configuration influences vulnerability. This study found that vulnerability was most readily identified at the household level, rather than within a specific sub-group within the broader community, and in this regard, this study provides further support to the hypothesis that IDPs are often vulnerable, but as a group, aren't adequately homogenous to warrant preferential treatment prima facie. Rather, vulnerability in the urban context, whether experienced by IDPs, voluntary migrants, or long-time residents, must be considered at the household level, as an analysis of the risks vulnerable groups face in the city, balanced against the means and mechanisms they employ to mitigate those risks.; Thesis (M.A.)--Tufts University, 2009.